Artificial intelligence without mathematics, is it possible? (Publicaciones en Ciencias y Tecnología, 2025)
Artificial intelligence (AI) has advanced at a dizzying pace, permeating nearly every aspect of modern society. From the virtual assistants on our phones to the complex algorithms that drive decisions in financial markets, AI has become a transformative force. Often, its capabilities seem almost magical, conjuring up images of science fiction and futuristic robots. However, behind this facade lies a solid, fundamental foundation: mathematics. The question many are asking is whether artificial intelligence could exist and make significant progress without recourse to mathematical principles. This analysis attempts to explain that mathematics is not simply a useful tool for AI, but constitutes its very essence, making the development and significant advancement of artificial intelligence without mathematical foundations an impossibility for deep understanding and real progress.
Keywords: Editorial; Artificial Intelligence; Mathematics